Measuring Facilities Management Practice and Consumers' Satisfaction: A Case Study of Shopping Malls in Sarawak - Adibah, Yusuf; Khairul Aidil Azlin, Abd Rahman; Wan Noor Faaizah, Wan Omar; Nadzirah, Yusuf; Farah, Zaini; Nangkula, Utaberta; Adam Andani, Mohammed (EAI, 2021)
This article intends to impart a clearer perception on the satisfactory on consumers' experiences in shopping malls from the facilities management (FM) practices perspective. In achieving commercial prosperity, shopping malls often neglect their obligation to fulfill consumers' satisfaction experience. Therefore, an integration between Mall and the FM is crucial in order to create functionality and provide significant value to the business and meet consumers' expectations. This study is designed to evaluate the physical facilities of selected shopping malls in Sarawak and to determine the aspects which contribute to the malls' success in meeting consumer needs. Visits to two selected malls and thorough observation of their facilities were documented as findings. A survey on facility management methods in malls was distributed to consumers who visits the selected malls and the results were analysed to determine the study's significance. The findings revealed that physical facilities of the mall, as well as consumer satisfaction, play a role on the reason people prefer one mall over another.